2011
DOI: 10.4067/s0718-58392011000300012
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Activity of Crop Residue Incorporation Alone or Mixed Against Rice and its Associated Grass Weed Jungle Rice (Echinochloa colona [L.] Link)

Abstract: Weed suppression is one of the several benefits achieved by soil incorporation of crop residues and such suppression is believed to be allelopathic in nature. The allelopathic potential of different crop residues: viz. sorghum (Sorghum bicolor [L.] Moench), sunflower (Helianthus annuus L.), brassica (Brassica campestris L.) was evaluated in rice (Oryza sativa L.) and jungle rice (Echinochloa colona [L.] Link). Chopped crop residues were soil-incorporated alone and mixed at 6 g kg-1 soil (12 t ha-1) and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Only on 5 th day the utmost germination observed (Table 1 and 2). This result correlates with the results of Khaliq et al (2011), where delayed seed germination observed in rice treated with crop residues of sorghum, sunflower and brassica. In the present study, phytotoxicity of both plants is presented in Figure 1 and 2.…”
Section: Resultssupporting
confidence: 78%
“…Only on 5 th day the utmost germination observed (Table 1 and 2). This result correlates with the results of Khaliq et al (2011), where delayed seed germination observed in rice treated with crop residues of sorghum, sunflower and brassica. In the present study, phytotoxicity of both plants is presented in Figure 1 and 2.…”
Section: Resultssupporting
confidence: 78%
“…Crop residues can suppress weeds through physical hindrance, or by posing chemical effects (allelopathy). Wheat is a potent allelopathic crop [14] and inhibitory effects of wheat residues upon decomposition to certain weeds have been well documented [14][15][16]. Incorporation of crop residues suppresses weeds through the release of phytotoxins [16], while mulching of crop residues produces a smothering effect on weeds [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although efficient, the judicious use of herbicides has also been questioned since it is widely believed that they cause resistance in some previously susceptible weed species; serious environmental concerns also arise due to their high residual effects in the soil (Ahn et al, 2005;Khaliq et al, 2011b). An international survey conducted in 70 000 fields revealed that over 383 biotypes of 208 weed species (122 dicots and 86 monocots) have evolved to be resistant to herbicides (Heap, 2012).…”
mentioning
confidence: 99%